USING FLIPBOOK MAKER TO CREATE SCIENCE PROCESS ORIENTED ELECTRONIC HANDOUT - Cahyani Rusdiana; Kaspul Kaspul; Nurul Hidayati Utami (ATRIUM PENDIDIKAN BIOLOGI, 2022)
E-handout is teaching material that are displayed electronically. One of the software used for e-handout development is Flipbook Maker. Mentioning the development of information technology, plus the proliferation of distance education, then the development of e-handout is one of the most appropriate choices. Moreover, its development is accompanied by Science Process Skills, so this development is carried out. This development research consists of 4 stages; define, design, develop and disseminate. This article contains research results in the form of values and descriptions of practicality test results. The research subjects were 9 practitioners from the State High School 8 Banjarmasin. The results of the study show that the e-handout is practical in the display aspect (score 88.88%), practical in the presentation aspect (88.00%), and practical also in the benefit aspect (88.21%). In conclusion, a product that is practically in line with expectations has been produced.